PERAN DIMENSI PELAYANAN PUBLIK DAN KEPERCAYAAN MASYARAKAT TERHADAP KPK DALAM MELAWAN KORUPSI - Prastyo, Yoga; Kurniansyah, Dadan; Adiarsa, Sopyan Resmana; Purnamasari, Hanny (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
Indonesia has designated its country as a country prone to corruption, this corruption is often carried out by officials and state officials who have high power, some corruption cases are very shocking to the public, this corrupt behavior is detrimental to the state and especially to the people or society itself, KPK (Corruption Eradication Commission), KPK as an organization responsible for eradicating corruption in Indonesia certainly has a very difficult task, especially since public trust in the institution is very high to be able to eradicate corruptors. This study was conducted with a qualitative approach, with a focus on analyzing public services implemented by the Corruption Eradication Commission (KPK) in an effort to eradicate corruption in Indonesia. The selection of qualitative methods is based on the need to gain an in-depth understanding of the concept of KPK public services. Results and Discussion Analysis of the Dimensions of KPK Public Service Quality is a critical step in exploring the commitment and success of the institution in providing quality and transparent services to the public. Through a careful approach to the five dimensions of service quality according to Tjiptono's SERVQUAL model (1996), namely Tangibles, Reliability, Responsiveness, Assurance, and Empathy, we can uncover the crucial elements that are the main foundation for the KPK. In analyzing the Tangibles dimension, it can be seen that the KPK shows its seriousness in providing public services by providing adequate facilities and infrastructure, creating positive physical evidence such as waiting rooms, X-Ray machines, and library rooms. In line with that, the Reliability dimension provides an overview of the quality of the KPK's reliability which is reflected in the statistics of the success of preventing and prosecuting corruption. Data from 2022 shows that the KPK has succeeded in handling 95% of reported corruption cases with significant penalties. This achievement is proof of the institution's consistency and accuracy in eradicating corruption, creating a high sense of public trust in the institution's reliability. . The conclusion can be emphasized that the KPK has succeeded in building a solid foundation in providing quality public services, which in turn affects public trust in this institution. From the results of the analysis of the dimensions of the quality of KPK public services, it can be concluded that the purpose of the study to understand the extent to which these dimensions affect public trust has been achieved